Measuring the Caregiver Burden of Caring for Community-Residing People with Alzheimer's Disease. - Hongmei Yu (PLoS ONE, 2015)
To assess the direct and indirect effects of patient or caregiver factors on caregiver burden of caring for community-residing people with mild Alzheimer's disease (AD).We conducted a cross-sectional study of patients diagnosed with AD from two hospitals and three communities in Taiyuan, China and their caregivers. For this survey, 200 patients with mild AD and their caregivers were selected. Caregivers were asked to provide sociodemographic information including age, gender, relationship with the patient, level of education, and number of contact hours per week with the patient. Caregiver burden was assessed using the Caregivers Burden Inventory. The caregivers also completed other measures including the Positive Aspects of Caregiving, the Family Adaptation, Partnership, Growth, Affection, and Resolve, and the Social Support Rating Scale. The patients with AD completed the Montreal Cognitive Assessment; their caregivers completed the Activities of Daily Living Scale and a questionnaire about the patients' Behavioral and Psychological symptoms of Dementia. The main outcome in this study was caregiver burden. The care receivers' level of cognitive function, physical function, and behavioral problems were treated as original stress; the primary appraisal variable was measured as the number of hours of caregiving in the previous week reported by the caregiver. Mediator variables included perceived social support, family function, and caregiving experience. Path analysis was used to build the interrelationship among caregiver burden and patient or caregiver factors.A lower level of cognitive function in patients (r = -0.28, p<0.001) and longer hours of caregiving (r = 0.17, p = 0.019) were related to increased caregiver burden. Greater social support (r = -0.23, p<0.001), family function (r = -0.17, p = 0.015) and caregiving experience (r = -0.16, p = 0.012) were related to decreased caregiver burden. Social support (r = 0.16, p = 0.040) and family function (r = 0.25, p = 0.002) were directly related to patients' level of cognitive functioning, but were mediator factors between level of cognitive function in patients and caregiver burden. Similarly, social support was a mediator factor between patients' daily function (r = -0.23, p = 0.004) and caregiver burden; while caregiving experience mediated the link between behavioral and psychological symptoms in patients (r = 0.36, p<0.001) and caregiver burden.Level of cognitive function and hours of caregiving were directly related to caregiver's burden. Social support, family function and caregiving experience could mediate the relationship between patient factors and caregiver burden. Focusing on patient factors and promoting caregiver care will be helpful in lowering the perceived burden of caregiving.